Balaustium medicagoense Meyer & Ryke, 1959 newly discovered in New Zealand (Acari: Erythraeiddae): descriptions of all life stages - Xu, Si-Yuan; Zhang, Zhi-Qiang (Zootaxa, 2020)
Balaustium medicagoense Meyer & Ryke, 1959 is reported from New Zealand for the first time. Field collected specimens were reared successfully on pollen grains of Typha orientalis in the laboratory. All life stages of this species are described and illustrated from laboratory-reared specimens as well as field-collected specimens.